Microstructures and Softening Behaviours of Lead Sinters and Their Correlation to Sintering Temperatures in Mount Isa Lead Smelter - Burrows. A. (Canadian Institute of Mining, Metallurgy and Petroleum, 2008)
Temperature profiles in the lead smelter sinter bed at Xstrata Zinc Mount Isa sinter plant have been measured using a wireless temperature probe. Corresponding sinter samples have been collected for characterization. The sinter peak bed temperatures were found to be in the range of 1000 - 1200 °C. Microstructures and softening temperatures of these sinters have been characterised. Strong correlations have been observed between peak bed temperature and peak hood temperature, and between mean sinter softening temperature and peak bed temperature. It was found that higher peak bed temperature results in higher sinter softening temperature. For the feed material used in the trials, to obtain sinters with mean softening temperatures above 1050 °C, peak bed temperatures above 1130 °C are required. There appears to be a direct correlation between granule size distribution in the feed and peak bed temperature attained. High peak bed temperatures are observed in sinters with narrow granule size distribution.